Pengaruh Pembelajaran Prakarya dan Kewirausahaan, serta Literasi Ekonomi terhadap Intensi Berwirausaha dengan Efikasi Diri sebagai Variabel Mediasi pada Siswa SMAN di Ciracas - Fadhilah Alwan; Aditya Pratama; Suparno Suparno (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of Craft and Entrepreneurship Learning as well as economic literacy on entrepreneurial intention, with self-efficacy as a mediating variable among senior high school students in Ciracas, East Jakarta. The research is grounded in the issue of low entrepreneurial intention among students based on preliminary survey results, and the persistently high unemployment rate among high school graduates. This study adopts a quantitative approach using a survey method through questionnaires distributed to 11th-grade students from three schools: SMAN 99, SMAN 58, and SMAN 105 Jakarta. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate that both Craft and Entrepreneurship Learning and economic literacy have a positive effect on self-efficacy and entrepreneurial intention. Moreover, self-efficacy is proven to be a significant partial mediating variable in the relationship between the independent variables and entrepreneurial intention. This research recommends strengthening entrepreneurship education and improving economic literacy in schools as strategies to foster students’ confidence and entrepreneurial spirit from an early age.